Free flap head and neck microsurgery with VITOMⓇ 3D: Surgical outcomes and surgeon's perspective. Issue 3 (June 2021) - Molteni, Gabriele; Nocini, Riccardo; Ghirelli, Michael; Molinari, Giulia; Fior, Andrea; Veneri, Antonio; Nocini, Pier Francesco; Marchioni, Daniele
Abstract: Objective: To report on the application of the 3D exoscopic system to microsurgery in a cohort of head and neck cancer patients; to analyse the performance of microvascular anastomoses, flap harvesting and insetting under exoscopic view and to evaluate the surgeon's feedback after procedures. Methods: An observational study was performed on 10 consecutive patients undergoing exoscopic microsurgical free flap reconstruction. The VITOM Ⓡ 3D system was applied to all procedures for microsurgical anastomoses, flap harvesting and insetting. Data about the type of resection and reconstruction, intraoperative and post-operative complications were recorded. Surgeon's feedback on exoscopic experience was collected through a questionnaire. Results: Reconstruction after oncologic demolition was performed by radial forearm flap in 3 cases (30%), antero-lateral thigh flap in 4 cases (40%), composite fibula flap in 2 cases (20%) and chimeric scapula flap in 1 case (10%). The mean surgical time for the microsurgical anastomoses (1 vein and 1 artery) was 34 min (range: 32–38). No intraoperative complications occurred and only two patients experienced pharyngo-cutaneous fistula in the post-operative time. There were neither cases of loss of flap, nor need of surgical revision. None of the cases had to be converted to OM technique. The surgeon never experienced back/neck pain, headache and nausea/vertigo. Occasionally, he felt tired and stressed and he reported eyestrain after one procedure only. Conclusions: VITOM Ⓡ 3D is easy to apply in the field of head and neck microsurgery and provides optimal stereoscopic view and anatomical details. Further studies are needed to validate indications and advantages of 3D exoscope as compared to OM.